ANALYSIS OF EARLY CHILDHOOD LANGUAGE DEVELOPMENT THROUGH STORYTELLING ACTIVITIES - Maria Fatima Mardina Angkur (INJOSEDU: International Journal of Social and Education, 2026)
Early childhood language development represents a foundational aspect of cognitive, social, and emotional growth. Storytelling activities are widely recognized as a pedagogical strategy that stimulates linguistic competence by fostering vocabulary acquisition, narrative comprehension, listening skills, and expressive communication. This study aims to analyze the role of storytelling activities in supporting early childhood language development using a literature review approach. Relevant scholarly articles, books, and empirical studies published in the fields of early childhood education, developmental psychology, and language acquisition were systematically examined. The review highlights that storytelling provides rich linguistic input, encourages interaction, enhances imagination, and strengthens children’s ability to structure thoughts verbally. Findings from the literature consistently indicate that storytelling contributes positively to both receptive and expressive language skills, including improvements in vocabulary breadth, sentence formation, phonological awareness, and conversational abilities. Furthermore, storytelling is shown to promote socio-emotional engagement, which indirectly supports communication confidence. The study concludes that storytelling activities constitute an effective, developmentally appropriate intervention for optimizing early language growth. Implications emphasize the need for educators and parents to integrate structured, interactive storytelling practices within early childhood learning environments.